The Impact of Extending Working Lives on Youth Employment in Great Britain: Research. Issue 1 (2nd January 2020) - Wels, Jacques
ABSTRACT: The article investigates the association between youth and older workers' employment participation in the United Kingdom using yearly data provided by the Labor Force Survey. Presenting a short state of the art, the paper shows that, with few exceptions, empirical analyses usually assume that increasing the labor market participation of the older workers does not affect negatively youth employment. Nevertheless, testing several variables and three different statistical models, the empirical part of the article nuances this evidence. The association between youth employment participation and older workers' employment participation tends to be significantly after controlling for public policy outcomes.